Artificial Intelligence Chatbot for Customer Service in E-Commerce Using Telegram Based on Node.js - Nabyla, Fuaida; Saraswati, Nurul Mega; Nursetyo, Arif; Hariyono, Rito Cipta Sigitta; Septi, Ariani Dwi ((JAIS) Journal of Applied Intelligent System, 2024)
Currently, the traditional market is increasingly being supplanted by numerous online markets. The fierce competition in the online market necessitates excellent service from sellers to buyers. As a result, many online stores now offer round-the-clock service, which can be financially burdensome if handled manually. Chatbots offer a promising solution by automating the online shopping process, thereby reducing costs and enhancing customer service. To address the need for accurate and prompt responses, this study proposes an intelligent chatbot system built on Artificial Intelligence (AI), specifically tailored to function as an e-commerce assistant. Integrated seamlessly into the Telegram application, the chatbot efficiently processes user input questions through three essential stages: parsing, pattern matching, and data crawling, all powered by AI technology. Within the AI process, user requests are systematically categorized into three primary domains: general questions, calculations, and stock checks. Notably, the calculation category encapsulates both order and payment processes. The effectiveness of the proposed method is substantiated by the results of 200 trials, demonstrating its adeptness in accurately addressing all user inquiries.